2013
DOI: 10.1186/1475-2840-12-103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FTO RS9939906 and MC4R RS17782313 on obesity, type 2 diabetes mellitus and blood pressure in patients with hypertension

Abstract: BackgroundGenetic variants of the FTO gene rs9939609 A/T and the MC4R gene rs17782313 C/T have been associated with obesity. Individuals with mutations in MC4R gene have lower blood pressure (BP), independently of obesity. This study aimed to investigate the association of FTO rs9939609 and MC4R rs17782313 with anthropometric indexes, BP, and type 2 diabetes mellitus among hypertensive patients.MethodsWe genotyped 217 individuals (86 men and 131 women) with hypertension (systolic or diastolic BP ≥ 140/90 mmHg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 45 publications
(57 reference statements)
3
45
0
3
Order By: Relevance
“…With regard to MetS, the studied association with the MC4R rs17782313 polymorphism disappears after adjusting for WC, indicating that the association with MetS is driven by the association with this factor 22. Moreover, studies on males proved that the rs17782313 polymorphism is associated with lower HDL concentration23 and elevated DBP 14,24…”
Section: Introductionmentioning
confidence: 98%
“…With regard to MetS, the studied association with the MC4R rs17782313 polymorphism disappears after adjusting for WC, indicating that the association with MetS is driven by the association with this factor 22. Moreover, studies on males proved that the rs17782313 polymorphism is associated with lower HDL concentration23 and elevated DBP 14,24…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, the MC4R V103I and I251L polymorphisms are associated with reduced risk of obesity. The polymorphism rs17782313, mapped 188 kb downstream from MC4R, is strongly associated with obesity and higher body mass index (BMI) (Frayling et al 2007;Loos et al 2008;Vogel et al 2011) alone or in association with other obesity-related genes, such as FTO (Marcadenti et al 2013). A GWAS study of 60,000 adults indicated that rs17782313(C) alleles are associated with higher BMI, with even greater effect in children.…”
Section: Introductionmentioning
confidence: 99%
“…FTO rs9939609 are strongly associated with obesity and T2D [29]. T2D, insulin resistance, and hypertension as cardiovascular risk factors were associated with the risk allele A for FTO rs9939609 [13].…”
Section: Discussionmentioning
confidence: 94%
“…Li et al [29] reported that FTO is associated with an increased risk of obesity and T2D, and FTO association with T2D is independent of BMI. Finally, Marcadenti et al [13] reported that common genetic variants of FTO rs9939609 have positive associations with BMI in women, but a negative association with diastolic and mean blood pressure in men with hypertension.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation